1994
DOI: 10.1093/oxfordjournals.humrep.a138348
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Evaluation of transvaginal sonography combined with a urinary luteinizing hormone monitor in timing donor insemination

Abstract: There remains controversy as to the most accurate method of predicting ovulation for the timing of donor insemination. In a prospective study based at a tertiary referral donor insemination clinic we have assessed the ability of a urinary luteinizing hormone (LH) kit combined with vaginal ultrasonography to predict ovulation for donor insemination. A total of 25 natural cycles were monitored from the first day of the LH surge (detected by the urinary kit). Daily transvaginal sonographic measurement of follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Transvaginal sonographic estimation of the follicular diameter and detection of LH in the urine by LH kits are commonly used methods of attempting to predict ovulation (10). Monitoring by transvaginal sonography is a non-invasive office technique with a pitfall resulting from the wide variation in the pre-ovulatory follicle size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transvaginal sonographic estimation of the follicular diameter and detection of LH in the urine by LH kits are commonly used methods of attempting to predict ovulation (10). Monitoring by transvaginal sonography is a non-invasive office technique with a pitfall resulting from the wide variation in the pre-ovulatory follicle size.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary LH monitoring also has limitations with occurrence of false negative and positive results. Irons and Singh (10) found that some women might ovulate before LH can be detected in the urine. When LH kits alone were used, in 9% of the women the urinary LH surge was detected after the follicle rupture was demonstrated by ultrasonography (12).…”
Section: Discussionmentioning
confidence: 99%
“…This has been found in up to 35% of ovulatory cycles [37]. It is possible that up to a third of inseminations are timed incorrectly when LH kits alone are used to time IUI [38] and some women may even ovulate before LH can be detected in the urine [39]. In addition, the small size of the study may have limited the detection of a small but significant difference in outcome.…”
Section: Discusionmentioning
confidence: 99%
“…It has even been reported that 12% of normal ovulatory women have LH peak values of <20 IU/l, 23% of ovulatory cycles have peak levels of 21-40 IU/l, and 38% of women have surges of <10 h in duration (Arici et al, 1992;Zreik et al, 1999). Moreover, some studies estimate that up to a third of IUI are timed incorrectly with urinary LH kits (Lloyd and Coulman, 1989), with up to 15% of women ovulating before the LH peak (Irons and Singh, 1994). Our cancellation rate of 19.1% in the u-LH group is comparable to the rates reported in the literature (23-32% of ovulatory cycles) (Cantineau et al, 2014;Lewis et al, 2006;Mitwally et al, 2004;Zreik et al, 1999), and was significantly higher than the US/HCG group.…”
Section: Discussionmentioning
confidence: 99%